Complexity and document: the hybridization of mediations in areas undergoing rupture - DOI: 10.3395/reciis.v3i3.274en - Viviane Couzinet (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
To complete communication between researchers studies and science popularization studies a new way in scientific communication is open by the author, the one between professionals and researchers. In this exchange area, often considered like a breakdown area, the information science research group of Toulouse University (France)analyse the hybridations in the mediations building. This posture allows to analyse numerous phenomenons and to reinvestigate the concept of document as a social construction.